Description of the first larval instar of Broscus crassimargo Wollaston, 1865 (Carabidae: Broscini) and notes about the presence of the species in the mesovoid shallow substratum of La Gomera (Canary Islands, Spain) - Gilgado, José; López, Heriberto; Oromí, Pedro; Ortuño, Vicente (Entomologica Fennica, 2011)
The first larval instar of the ground beetle Broscus crassimargoWollaston, 1865 endemic to La Gomera (Canary Islands, Spain) is described. This is the first comprehensive study of the primary chaetotaxy of the three tagmata ever carried out in larvae of Broscini, being also accompanied by a detailed iconography. The implications of the results of this chaetotaxy analysis are discussed in relation to the possible origin of Broscini within Carabidae. Comments on the ecological determinants for its remarkable presence in the mesovoid shallow substratum are given, analysing the differences between La Gomera and other Canary islands where samplings in the same subterranean habitat have been carried out.